The Impact of the Philosophical Attitudes of Primary Level Islamic Education Teachers on the Value System of Their Students - Hamdan, Eyad Saad Ibrahim; Al-Kilani, Ahmed Mohieddin (Dirasat: Educational Sciences, 2023)
Objectives: This study examines the influence of philosophical attitudes held by primary level Islamic Education teachers on their students' value system. Methods: The research employed a descriptive survey method, with a sample comprising 97 Islamic education teachers and 873 male and female students from public schools in the Directorate of Education in Marka, Jordan. The study utilized questionnaires to assess the teachers' philosophical attitudes (ideal, pragmatic, and Islamic) and to identify students' value system across ethical, social, and behavioral domains. Results: The results indicated a significant impact of teachers' philosophical attitudes on students' values, with moral values ranked highest, followed by behavioral and social values. Additionally, no statistically significant differences were found in teachers' philosophical attitudes based on gender, but variations were observed concerning scientific qualification, experience, and adherence to Islamic philosophy. Conclusion: The study concludes by recommending qualitative and quantitative assessments of teachers' awareness of their educational philosophies and suggests organizing seminars and training programs to enhance teachers' understanding of different educational philosophies and their implications on the educational process. Furthermore, the study proposes that development programs for Islamic education teachers should emphasize the importance of the value system and effective methods of teaching and learning it.